2022
DOI: 10.1002/cbin.11809
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of YAP attenuates pericyte‐myofibroblast transition and subretinal fibrosis in experimental model of choroidal neovascularization

Abstract: Age‐related macular degeneration (AMD) is the main reason of irreversible vision loss in the elderly. The subretinal fibrosis subsequent to choroidal neovascularization (CNV) is an important feature in the late stage of wet AMD and is considered to be one reason for incomplete response to anti‐VEGF drugs. Recent studies have shown that pericyte‐myofibroblast transition (PMT) is an important pathological process involving fibrotic diseases of various organs. However, the specific role and mechanism of PMT in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…In our previous bioinformatics analysis, 27 DEGs were highly enriched in the MAPK signaling pathway, including MAPK9, MAPK11, MAPK13, MAPK14, MAPK8IP1 and MAPK8IP2 (data not shown). Some studies have demonstrated that the MAPK signaling pathway may participate in neural or cardiovascular pericyte differentiation [ 67 69 ], but whether the TGF-β1/MAPK pathway participates in renal pericyte metabolism and differentiation needs further study.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous bioinformatics analysis, 27 DEGs were highly enriched in the MAPK signaling pathway, including MAPK9, MAPK11, MAPK13, MAPK14, MAPK8IP1 and MAPK8IP2 (data not shown). Some studies have demonstrated that the MAPK signaling pathway may participate in neural or cardiovascular pericyte differentiation [ 67 69 ], but whether the TGF-β1/MAPK pathway participates in renal pericyte metabolism and differentiation needs further study.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanisms of subretinal fibrosis secondary to nAMD are complicated and remain incompletely elucidated. Extensive literature corroborated the involvement of additional factors, such as pericyte-myofibroblast transition (PMT) [ 53 ], EndMT [ 54 ], activated microglia [ 55 ], macrophages [ 56 ] and Müller glia [ 57 ] in the laser-induced CNV mouse model, which contribute to the accumulation of differentiated myofibroblasts and deposition of ECM, ultimately leading to fibrosis formation in nAMD. Therefore, the contribution of Wnt5a or Wnt/β-catenin in the MT of other cell types during subretinal fibrosis remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, YAP is connected to the mitogen‐activated protein kinase (MAPK)/ERK pathway, participates in pericyte‐myofibroblast transition and promotes CNV fibrosis 24 . In a laser‐induced CNV mouse model, YAP knockdown not only reduced the proliferation, migration and differentiation of human retinal microvascular pericytes but also attenuated pericyte‐myofibroblast transformation and subretinal fibrosis 24 . These findings highlight the role of the Hippo pathway in AMD, and identify YAP/TAZ as possible targets for preventing AMD‐related neovascularization and subretinal fibrosis.…”
Section: Hippo Signalling Pathway In Eye Diseasesmentioning
confidence: 99%
“…Recent studies have demonstrated that pharmacological inhibition or genetic depletion of YAP attenuates hypoxia‐ or TGF‐β2‐induced inflammation and EndMT in HUVECs, and reverses laser‐induced subretinal fibrotic changes in mouse models, providing a new therapeutic target for the treatment of subretinal fibrosis in wet AMD 75,86,87 . Additionally, YAP is connected to the mitogen‐activated protein kinase (MAPK)/ERK pathway, participates in pericyte‐myofibroblast transition and promotes CNV fibrosis 24 . In a laser‐induced CNV mouse model, YAP knockdown not only reduced the proliferation, migration and differentiation of human retinal microvascular pericytes but also attenuated pericyte‐myofibroblast transformation and subretinal fibrosis 24 .…”
Section: Hippo Signalling Pathway In Eye Diseasesmentioning
confidence: 99%
See 1 more Smart Citation